(untitled) (Experimental biology, 2009)
Model of alloxan diabetes of rats made by way iniection alloxan. Influence of alloxan on morphological structure and functional state of lymphatic nodes of rats was studied. Lymph transport and biochemical composition of lymph decreased. Introduction of α-tocoferol and soy-bean milk to alloxan diabetes rats revealed positive effect on morfofunctional state of lymphatic system and depressed the development of alloxan diabetes.